The effect of chronological age on the inflammatory response of human fibroblasts - Wolf, Juliane (Elsevier Science, 2012)
The immune system undergoes profound age-related changes, including a gradual increase in the production and circulation of proinflammatory cytokines. Despite the known capacity of fibroblasts to produce cytokines, little is known so far about the inflammatory response of fibroblasts to cellular stress such as viral and/or bacterial infection in the context of aging. Therefore the aim of this study was to analyze the levels of IL6 and IL8 secretion in supernatants of human skin fibroblasts from young and elderly persons. Cytokine and chemokine secretion was analyzed before and after in vitro infection of the cells with Cytomegalovirus (CMV) and/or stimulation with Lipopolysaccharide (LPS). The exposure of fibroblasts to these agents caused inflammatory changes, reflected by the secretion of both the cytokine IL6 and the chemokine IL8 by fibroblasts from young as well as elderly persons. The cytokine/chemokine production induced by either agent alone could be further increased by co-stimulation of the cells with both stimuli. The level of protein secretion was dependent on the chronological age of the fibroblasts. Stimulated human skin fibroblasts from elderly donors produced higher amounts of IL6 as well as IL8 than fibroblasts from young donors. These differences were more pronounced for IL6 than for IL8. The inflammatory response of fibroblasts to stimulation differed among donors and did not correspond to the responsiveness of whole blood derived from the same person. In summary lifelong CMV-infection may act as an in vivo trigger for inflammatory changes by increasing the inflammatory response to bacterial products such as LPS. It may thus contribute to age-related inflammatory processes, referred to as ‘inflamm-aging’.